Equivalence revisited: a key concept in modern translation theory (2002)
This paper attempts to discuss the importance, relevance and validity of the concept of equivalence as a constitutive notion in translation theory. Equivalence is defined as a relation that holds between a Source Language (SL) text and a Target Language (TL) text. Our conception of equivalence is supported by a modern text-linguistic theory that considers that the text is the unit of analysis of the communicative event and, as translation itself is seen as a communicative event, then logically, it should be studied from a modern textlinguistic approach. A brief background is provided to support this perspective. However, this is a point of view not necessarily shared by all modem translation theorists and, therefore, two antagonistic positions in translation theory as well as the criticism against Linguistics/Text-oriented Theories (TOT) are analyzed. Then arguments for and against the notion of equivalence within tot and cot (Non-Linguistics/Context-oriented Theories) are discussed in detail and new perspectives reviewed. Finally, equivalence within the framework of a Dynamic Translation Model (DTM) is discussed and a brief illustration of its application in translation criticism is provided.